PERCEPTIONS OF UNIVERSITY STUDENTS REGARDING THE EFFECTS OF ENVIRONMENTAL ISSUES ON HEALTH (Turkey Health Literacy Journal, 2024)
Purpose: In this study, the aim is to better understand university students’ perceptions of the potential impacts of environmental issues on health and to examine how this may influence future environmental policies and individual behavioral patterns. Method: The research is a descriptive type of survey study. The study included 232 university students. The data were analyzed using, SPSS 23 software. Significance level of p<0.05 was considered. Results: 84.1% of the participants believe that there are environmental issues in their living environment. 0.9% of the participants never, 6.5% rarely, 43.1% sometimes, 29.7% often, and 19.8% always perceive that environmental problems can harm health. Individuals with chronic diseases more often perceive that environmental issues can harm health compared to those without such diseases. Those who believe in environmental pollution problems in their living environment are also more likely to perceive that these issues frequently or always affect health compared to non-believers. Conclusion: Our study shows high environmental awareness among participants, yet reveals gaps in understanding the impact of environmental conditions on health. Recognizing the link between environmental issues and health is vital for sustainability and community well-being. Thus, promoting environmental health literacy is crucial to raise awareness and consciousness about environmental matters.